Critique of Materialism in ‘Ilm al-Kalām al-Jadīd: An Analysis of Jamaluddin al-Afghani’s Thought - Muhammad Arwani Rofi'i; Siti Fatimatuz Zahroh; Nodir Tolipov (Journal of Islamic and Occidental Studies, 2025)
This article examines the concept of materialism from the perspective of ‘ilm al-kalām al-jadīd, focusing on the thought of Jamaluddin al-Afghani. It critically analyzes al-Afghani’s response to the rise of materialism in the 19th century within philosophical and theological debates in the Islamic world. The main objective of this study is to explain how al-Afghani formulated his critique of materialism and how his ideas contributed to modern Islamic theology. Using qualitative methods and content analysis, the study explores al-Afghani’s works especially al-Radd ‘alā al-Dahriyyīn alongside relevant secondary sources. The findings show that al-Afghani regarded materialism as a serious threat to moral and spiritual life because it rejects metaphysical elements such as God, the soul, and the afterlife. He argued that materialism weakens the ethical role of religion and leads to spiritual decline in Muslim society. Within modern kalām, al-Afghani sought to integrate Islamic theology with contemporary intellectual challenges without abandoning core principles. His critique significantly influenced modern Islamic thought by encouraging theological commitment while engaging with modernity